2019
DOI: 10.1021/acs.cgd.9b00152
|View full text |Cite
|
Sign up to set email alerts
|

Homochiral Porous Metal–Organic Frameworks Constructed from a V-Shaped Alanine Derivative Based on Pyridyl-Dicarboxylate

Abstract: Three novel, homochiral, porous metal–organic frameworks based on the H2PDBAla ligand and different divalent cations (Co­(II)) and Cu­(II)), namely, [M­(PDBAla)­(bipy)­(H2O)2]­·3H2O (M = Co 1 and Cu 2), [Cu­(PDBAla)­(bpea)]­·7H2O (3) (H2PDBAla = pyridine-2,6-dicarbonyl-bis­(l-alanine), bipy = 4,4′-bipyridine, bpea = 1,2-bis­(4-pyridyl)­ethane), have been synthesized and characterized with the assistance of N-donor ligands. The distinctive H2PDBAla ligands are coordinated to divalent metal ions by the different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 59 publications
(67 reference statements)
0
6
1
Order By: Relevance
“…The materials showed good CO 2 adsorption performance and the [Cu(PDBAla)(bpea)] • 7H 2 O was further used for enantioselective separation of alcohols. [29] More recently, Zaworotko and coworkers utilized the linker R/S-mandelate to generate a family of 4 th generation chiral MOFs having rigid framework and flexible/adaptable pores; derived from the previously reported parent structure [Co 2 (S-mandelate) 2 (4,4'-bipyridine) 3 ](NO 3 ) 2 (CMOM-1S/R; CMOM: chiral metal-organic materials) in order to elucidate the mechanism of chiral selectivity in porous materials by altering through host-guest or guest-guest interactions using variable counterions (BF 4 À , CMOM-2S; CF 3 SO 3 À , CMOM-3S), or substitutions on organic linker (2-Cl, CMOM-11R; 3-Cl, CMOM-21R; 4-Cl, CMOM-31R; and 4-CH 3 , CMOM-41R). The structural analysis of these crystalline sponges revealed that a combination of host-guest, guest-guest interactions and the pore adaptability play an important role in determining the enantioseparation abilities of these MOFs with hard-soft features enabling the chiral discrimination.…”
Section: Chiral Mofs From Chiral Fragmentsmentioning
confidence: 99%
“…The materials showed good CO 2 adsorption performance and the [Cu(PDBAla)(bpea)] • 7H 2 O was further used for enantioselective separation of alcohols. [29] More recently, Zaworotko and coworkers utilized the linker R/S-mandelate to generate a family of 4 th generation chiral MOFs having rigid framework and flexible/adaptable pores; derived from the previously reported parent structure [Co 2 (S-mandelate) 2 (4,4'-bipyridine) 3 ](NO 3 ) 2 (CMOM-1S/R; CMOM: chiral metal-organic materials) in order to elucidate the mechanism of chiral selectivity in porous materials by altering through host-guest or guest-guest interactions using variable counterions (BF 4 À , CMOM-2S; CF 3 SO 3 À , CMOM-3S), or substitutions on organic linker (2-Cl, CMOM-11R; 3-Cl, CMOM-21R; 4-Cl, CMOM-31R; and 4-CH 3 , CMOM-41R). The structural analysis of these crystalline sponges revealed that a combination of host-guest, guest-guest interactions and the pore adaptability play an important role in determining the enantioseparation abilities of these MOFs with hard-soft features enabling the chiral discrimination.…”
Section: Chiral Mofs From Chiral Fragmentsmentioning
confidence: 99%
“…The amino acid derivatives based on the different natural amino acids and multifarious polycarboxylates have been found in a number of homochiral CPs. The structural difference of various natural amino acids and polycarboxylates may induce distinct and fascinating helical architectures. Meanwhile, the bifunctional groups of the −NH and the −CO moieties of amino acid derivatives could furnish two kinds of guest accessible active locations, which act as electron donors and acceptors, or act as the sites of Lewis acids and bases. These characteristics of amino acid derivatives could facilitate the creation of homochiral CPs with intriguing helical architectures and excellent properties. Nonetheless, the predictable design and construction of the functional homochiral CPs embedded helical motifs are a great challenge due to the uncontrollability of the self-assembled process.…”
Section: Introductionmentioning
confidence: 99%
“…21−23 The structural difference of various natural amino acids and polycarboxylates may induce distinct and fascinating helical architectures. Meanwhile, the bifunctional groups of the −NH and the −CO moieties of amino acid derivatives could furnish two kinds of guest accessible active locations, 24 which act as electron donors and acceptors, or act as the sites of Lewis acids and bases. These characteristics of amino acid derivatives could facilitate the creation of homochiral CPs with intriguing helical architectures and excellent properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the field of molecule-based magnets, the lanthanide­(III) ions in MOFs and CFs, especially the Dy 3+ ion, can exhibit superparamagnetic properties thanks to not only significant magnetic anisotropy but also large magnetic moments, , such as single-molecule magnet (SMM) properties that make LnCPs and LnMOFs potential applications in the fields of information storage and molecular device. However, owing to the characteristics of ferroelectricity , and nonlinear optical activity, the chirality in molecular materials is highly valued, which is especially beneficial for multifunctional integration; moreover, homochiral MOFs may be used in not only heterogeneous asymmetric catalysis but also enantioselective separation. However, it remains a great challenge to obtain homochiral MOFs or homochiral CPs, especially homochiral LnCPs or homochiral LnMOFs. …”
Section: Introductionmentioning
confidence: 99%